Bacterial volatile compound-based tools for crop management and quality - Cellini, Antonio; Spinelli, Francesco; Donati, Irene; Ryu, Choong-Min; Kloepper, Joseph W. (Trends in plant science, 2021)
Bacteria produce a huge diversity of metabolites, many of which mediate ecological relations. Among these, volatile compounds cause broad-range effects at low doses and, therefore, may be exploited for plant defence strategies and agricultural production, but such applications are still in their early development. Here, we review the latest technologies involving the use of bacterial volatile compounds for phytosanitary inspection, biological control, plant growth promotion, and crop quality. We highlight a variety of effects with a potential applicative interest, based on either live biocontrol and/or biostimulant agents, or the isolated metabolites responsible for the interaction with hosts or competitors. Future agricultural technologies may benefit from the development of new analytical tools to understand bacterial interactions with the environment. Plant-associated bacteria interact with their environment through the exchange of chemicals, including volatile compounds. Innovative agricultural technologies may exploit the inherent advantages of bacterial airborne signals, including diffusibility, independence from water availability and physical connection, and absence of pesticide residuals.Volatile compounds resulting from plant–pathogen interactions allow nondestructive disease diagnosis on bulk samples of asymptomatic plant material.Volatile compounds, expressing a direct biocidal activity, interfering with signalling, or stimulating plant host defences, contribute to the biological control of pests and pathogens.Bacterial volatile compounds modulate plant hormones enhancing plant growth, stress tolerance, crop quality, aroma and nutraceutical characteristics, and reduce post-harvest losses.